Everolimus-eluting stent platforms in percutaneous coronary intervention: comparative effectiveness and outcomes - Panoulas VF (Dove Medical Press, 2015)
Vasileios F Panoulas,1 Ioannis Mastoris,2 Klio Konstantinou,1 Maurizio Tespili,3 Alfonso Ielasi3 1National Heart and Lung Institute, Imperial College London, London, UK; 2Interventional Cardiovascular Research and Clinical Trials, The Zena and Michael A Wiener Cardiovascular Institute, The Icahn School of Medicine at Mount Sinai, New York NY, USA; 3Cardiology Department, Bolognini Hospital Seriate, Seriate (BG), Italy Abstract: Despite the remarkable benefits obtained following the introduction of the first-generation drug-eluting stent (DES), concerns were raised over its long-term safety, particularly with regard to very late (beyond 1 year) stent thrombosis. Newer-generation DESs have been developed to overcome this limitation using novel stent platforms, new drugs, more biocompatible durable polymers, and bioabsorbable polymers or backbones. To date, new-generation DESs have virtually replaced the use of first-generation DESs worldwide. In this review article, we discuss in detail the design, pharmacology, and mechanism of action of the newer-generation permanent and bioresorbable everolimus-eluting platforms. Furthermore, we present and evaluate the current evidence on the performance and safety of these devices compared to those of other available stent platforms. Keywords: PCI, angioplasty, stent, outcome